2016
DOI: 10.1016/j.jbiomech.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Time-elapsed screw insertion with microCT imaging

Abstract: 'This is the peer reviewed version of the following article: Ryan MK, Mohtar AA, Cleek TM, Reynolds KJ. Time-elapsed screw insertion with microCT imaging. Journal of Biomechanics. pii: S0021-9290(15)00727-7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Second, the width of unloaded fracture gaps was not correlated with the type of repair at every measurement site. Had previous compression resulted in permanent bone volume reduction, this would have been most apparent at the mid P1 site because any change in trabecular bone volume is typically restricted to within a few millimeters of the implant . Had this effect been present, the triangular repair should have been associated with a smaller fracture gap grade at this site; however, this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…Second, the width of unloaded fracture gaps was not correlated with the type of repair at every measurement site. Had previous compression resulted in permanent bone volume reduction, this would have been most apparent at the mid P1 site because any change in trabecular bone volume is typically restricted to within a few millimeters of the implant . Had this effect been present, the triangular repair should have been associated with a smaller fracture gap grade at this site; however, this was not the case.…”
Section: Discussionmentioning
confidence: 98%
“…All D values were zeroed at a starting F value of 5 N to eliminate the initial "slack" effect in tests. Relaxation of bone material during microCT scans was shown in similar axial loading studies 32,34 to produce local dips in force values but to not affect the overall shape or maximum values of the F-D curve. These findings were confirmed in a pilot study (Supplementary Materials).…”
Section: Discussionmentioning
confidence: 81%
“…Indenters were fabricated from 5.0 mm diameter rods of 6061‐T6 aluminum, selected for its radiolucency. A review of the literature indicated that the yield strength and elastic modulus of the material (250 MPa and 70 GPa, respectively) would provide satisfactory rigidity given the stresses anticipated during the experiment. Rods were cut into 40 mm segments, and one end of each segment was precision lathed to add either a flat or sharp/conical tip (55° vertex angle) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This may be related to the very limited area over which trabecular deformation occurs with screw tightening. 10 There were a number of limitations in this study. First, the cadaveric simulated arthrodesis used in this study only models the behavior of bone at the time of surgery.…”
Section: Discussionmentioning
confidence: 92%